Performance enhancement of poly (lactic acid)/soy protein concentrate blends by promoting formation of network structure. Issue 3 (1st September 2013) - Liu, Linshu; Liu, Bo; Zhang, Jinwen; Guevara, Gabriel Z.
Abstract : In this study, effects of water content in the preformulated soy protein concentrate (SPC) and SPC content on thermal, rheological and mechanical properties and morphology of poly(lactic acid) (PLA)/SPC blends were studied. The blends were prepared by twin screw compounding and the test specimens were injection molded. Water in the preformulated SPC was a critical factor for the development of SPC phase structure in the blends. The results indicated that the preformulated SPC containing water experienced large deformation during compounding and formed interconnected network structure in the resulting blends. Dynamic mechanical analysis revealed that the addition of water in the preformulated SPC and increasing the SPC loading level greatly improved the storage modulus of the resulting PLA/SPC blends at elevated temperatures.